Consumers' Attitude towards Consumer Protection in the Digital Single Market, as Reflected by European Barometers - Pleșea Doru Alexandru; Maiorescu Irina; Cîrstea Alice (Amfiteatru Economic Journal, 2014)
The European Single Market is an ongoing project that will continue to further develop and adapt to changing realities. Traditional economic activities, and the administrative rules governing them, face the challenge of adapting to developments that blur the dividing lines, for example, between shop and online sales or between traditional media and Internet communication.
Keywords: D18; L81; F15; 330; consumer's trust; consumer protection; e-commerce; digital single market; awareness of consumer legislation; cross-border shopping; consumer's certainty and decisional capacity